2021
DOI: 10.48550/arxiv.2112.05967
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The study of double-charm and double-strange tetraquarks

Abstract: In the framework of the quark delocalization color screening model (QDCSM), we systematically investigate the double-charm and double-strange tetraquark systems ccss with two structures: meson-meson and diquark-antidiquark. The bound-state calculation shows that there is no any bound state in present work. However, by applying a stabilization calculation and coupling all channels of both two structures, two new resonance states with IJ P = 00 + are obtained. One is more possible to be a molecular resonance sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…This is not often the case of some other approaches. In particular, a lattice calculation [89] and some quark models [97][98][99][101][102][103] expect a mass of the T ccss and T bbss 0 + states well above the physical threshold while in our case the T bbss state lies below the physical threshold and the one of the T ccss 0 + state is slightly above (see Table 5). This peculiar feature of SU3 breakings for exotic states needs to be checked experimentally.…”
Section: Lsr ⊕ Drsr Confronted To Some Other Approachesmentioning
confidence: 52%
See 1 more Smart Citation
“…This is not often the case of some other approaches. In particular, a lattice calculation [89] and some quark models [97][98][99][101][102][103] expect a mass of the T ccss and T bbss 0 + states well above the physical threshold while in our case the T bbss state lies below the physical threshold and the one of the T ccss 0 + state is slightly above (see Table 5). This peculiar feature of SU3 breakings for exotic states needs to be checked experimentally.…”
Section: Lsr ⊕ Drsr Confronted To Some Other Approachesmentioning
confidence: 52%
“…In Fig. 25, we confront our results from LSR ⊕ DRSR with the ones from different approaches in the literature (lattice calculations [89][90][91][92], light front holographic [93], quark and potential models ⊕heavy quark symmetry [94][95][96][98][99][100][101][102][103]). We refrain to comment on the technical details of the estimates from different approaches being non-experts in these fields.…”
Section: Lsr ⊕ Drsr Confronted To Some Other Approachesmentioning
confidence: 99%
“…Recently, Belle Collaboration searched for the tetraquark state X ccss in D s D s (D * s D * s ) final states, but no significant signals were observed [190]. In the quark models [154,191], T ++ ccss , T + bcss , and T 0 bbss cannot form stable states because all interactions in the states cannot provide enough attraction because the ground state antidiquark s s cannot form a good antidiquark [28]. The lattice QCD investigations on the states T ++ ccss , T 0 bbss , and T + bcss indicated that no clear indication of any level below their respective threshold can be found [176].…”
Section: Isospin V-spin and U-spin Symmetrical Statesmentioning
confidence: 99%
“…The lattice QCD investigations on the isospin symmetric states indicated that no clear signal of any level below their respective thresholds can be found [176]. All of the isospin symmetrical states T + cc , T − bb , and T 0 bc and the V-spin symmetrical states T + ccs , T − bbs , and T 0 bcs cannot form stable states because all interactions in the states cannot provide enough attraction in the models [140,154,191]. The optimal spin-isospin-color-orbital combination of a good heavy diquark QQ and a good light antidiquark q q is a necessary condition to produce a stable double heavy tetraquark state from the perspective of diquarks [28].…”
Section: Isospin V-spin and U-spin Symmetrical Statesmentioning
confidence: 99%